Gastrostomy Placement in Children: Percutaneous Endoscopic Gastrostomy or Laparoscopic Gastrostomy?. Issue 5 (October 2016) - Merli, Laura; De Marco, Erika A.; Fedele, Camilla; Mason, Elena J.; Taddei, Alessandra; Paradiso, Filomena V.; Catania, Vincenzo D.; Nanni, Lorenzo
Abstract : The aim of this study is to compare the outcomes and the complications between the 2 most adopted procedures for gastrostomy placement: percutaneous endoscopic gastrostomy (PEG) and laparoscopic gastrostomy (LG) in children. We present our study on 69 patients (male: 46/female: 23): group 1 (37 patients, 54%) undergoing PEG, group 2 (32 patients, 46%) undergoing LG. A total of 5 major complications were observed all in the PEG group (13.5%), no major complication was observed in the LG group ( P -value<0.05). A total of 12 minor complications were observed: 4 occurred in the PEG group (10.8%) and 8 (25%) in the laparoscopic gastrostmoy group, not statistically relevant. We suggest that the LG should be considered the preferred technique for gastrostomy placement in pediatric patients, particularly in newborns, children with significant skeletal malformations, and patients who underwent previous abdominal surgery.